Роль українознавства у зміцненні української національної ідентичності та у впровадженні національно-патріотичного виховання в освітній простір під час російсько-української війни - Шакурова, Ольга (Київський національний університет імені Тараса Шевченка, 2024)
Проаналізовано роль українознавства у зміцненні української національної ідентичності та впровадженні національно-патріотичного виховання в освітній простір під час російсько-української війни. Висвітлено роль вчених-українознавців у цьому процесі.

Relevance of the research. Effective and efficient resistance to the aggressive policy of the Russian state can be carried out with the help of scientific justification and the creation of a professional complex of management decisions and measures that will be used to significantly strengthen the positive trends in the development of the Ukrainian state, the Ukrainian nation, the strengthening of Ukrainian national identity, and Ukrainian civil society. The implementation of national and patriotic education is, first of all, specific actions that representatives of the nation, educational and state structures can take to actualize Ukrainian national identity. The purpose of the research is to analyze the role of Ukrainian studies in strengthening the Ukrainian national identity and in introducing national-patriotic education of schoolchildren in the educational and humanitarian space of Ukraine during the war and to outline the role of scientists-Ukrainian studies in these processes. Conclusions. Thus, Ukrainian scholars actively, comprehensively, and systematically research various aspects of Ukrainian national identity as the basis of national-patriotic education, consistently and systematically introduce national-patriotic narratives into the educational and humanitarian space of Ukraine during the Russian-Ukrainian war. Their activity, which includes not only the scientific and theoretical understanding of the researched issues, but also the active practical implementation of national-patriotic education in the humanitarian and educational space of Ukraine by holding student competitions in Ukrainian studies and artistic student competitions, becomes an important factor in countering Russian aggression against Ukraine, helps consolidate the Ukrainian political nation and speeds up the victory of the Ukrainian state.
The Role of Ukrainian Studies in Strengthening the Ukrainian National Identity And Implementing the National and Patriotic Education in the Educational Space During the Russian-Ukrainian War
Keywords: Україна; українці; українознавство; національно-патріотичне виховання; українська національна ідентичність; російсько-українська війна; Ukraine; Ukrainian studies; Ukrainian national identity; national-patriotic education; Russian-Ukrainian war